Acupuncture for Chemoradiation Therapy-Related Dysphagia in Head and Neck Cancer: A Pilot Randomized Sham-Controlled Trial. (10th August 2016) - Lu, Weidong; Wayne, Peter M.; Davis, Roger B.; Buring, Julie E.; Li, Hailun; Macklin, Eric A.; Lorch, Jochen H.; Burke, Elaine; Haddad, Tyler C.; Goguen, Laura A.; Rosenthal, David S.; Tishler, Roy B.; et al.
Abstract : Introduction: Dysphagia is common in head and neck cancer patients after concurrent chemoradiation therapy (CRT). This study evaluated the feasibility of conducting a randomized sham-controlled trial and collected preliminary data on safety and efficacy of acupuncture. Patients and Methods: Head and neck cancer (HNC) patients with stage III–IV squamous cell carcinoma were randomized to 12 sessions of either active acupuncture (AA) or sham acupuncture (SA) during and following CRT. Patients were blinded to treatment assignment. Swallowing-related quality of life (QOL) was assessed using the MD Anderson Dysphagia Inventory (MDADI) total and subscale scores. Results: Multiple aspects of trial feasibility were confirmed. Forty-two of 196 patients screened (21%) were enrolled and randomized to receive AA ( n = 21) or SA ( n = 21); 79% completed at least 10 of 12 planned acupuncture sessions; 81% completed the study follow-ups. The majority of patients reported uncertainty regarding their treatment assignment, with no difference between the AA and SA groups. Audits confirmed both AA and SA treatments were delivered with high fidelity. No serious acupuncture-related side effects were observed. MDADI total scores significantly improved from baseline to 12 months post-CRT in both groups (AA: +7.9; SA +13.9; p = .044, p < .001). Similar patterns were observed for the MDADI global subscale (AA: +25.0; SA +22.7; p = .001, p = .002). Intent-to-treat analyses suggested no difference between the treatment groups ( p = .17, p = .76 for MDADI total and global scores, respectively). Conclusion: A sham-controlled randomized trial evaluating acupuncture in dysphagia-related QOL in HNC found the procedure to be feasible and safe. Further investigation is required to evaluate efficacy. Abstract : This study evaluated the feasibility of conducting a randomized sham-controlled trial and collected preliminary data on safety and efficacy of acupuncture. The study supports the finding that a sham-controlled randomized trial evaluating acupuncture in dysphagia-related quality of life in head and neck cancer is feasible and safe. Further investigation is required to evaluate efficacy.